The Resilience of Laid-Off Mothers of The Covid-19 Pandemic on Children's Learning Outcomes - Murniarti, Erni; Simorangkir, Melda Rumia Rosmery (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
The Covid-19 pandemic attacked all sectors including education, industry and the economy. The government's decision to lock down to slow the spread of Covid-19 has had a major impact on Indonesia. There are many companies, restaurants and other businesses that have had to go out of business, so unemployment has increased during the Covid-19 pandemic. The purpose of this study was to look at the mother's actions when she found out that she was a victim of layoffs, as well as the mother's efforts to meet the needs of children's learning media during school from home after being laid off. The method used is qualitative through a case study approach. Data collection techniques are carried out by documentation, interviews and observation. The research subjects were students and mothers of victims of layoffs in the Pulogadung industrial area, Jakarta. The results showed that maternal resilience greatly influences student learning outcomes, maternal resilience is needed to build maximum children's learning conditions. Even though they are in a very complicated situation due to layoffs due to the COVID-19 pandemic, mothers are willing to help themselves so that their children are helped both psychologically, physically and cognitively. Based on the results of observations, documentation and interviews, it can be concluded that the mental condition of the mother, in this case the resilience of the mother, greatly affects student learning outcomes, mother's resilience is needed to build maximum children's learning conditions. Even though they are in a very complicated situation due to the layoffs of the Covid-19 pandemic, mothers are willing to help themselves so that their children are helped both psychologically, physically and cognitively.